Exploitation Of Induced Variability For Crop Improvement In Ginger (Zingiber officinale Rosc.) - Shankar G (Department of Plantation Crops and Spices, College of Horticulture, 2003)
Investigations on "Exploitation of induced variability for crop improvement in ginger (Zingiber officinale Rosc.)" were carried out at Department of Plantation Crops and Spices and Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, V ellanikkara during 2001- 2003. Evaluation of seven induced variants along with three check varieties indicated the superiority of the autotetraploids V 2 (Z - 0 - 86) and V I (Z - 0 - 78) in quality attributes. V 2, an autotetraploid from Rio-de-Janeiro was notable for lowest fibre content, highest oil and oleoresin content and increased driage and high cuticle thickness than its diploid counterpart. V!, an autotetraploid from Himachal Pradesh exhibited highest driage, high oleoresin content and highest cuticle thickness. V 2 was more vigorous in growth exhibiting maximum yield contributing characters such as number of tillers per plant, number of leaves per plant, leaf area and also leaf area index and root length. V I showed maximum plant height and pseudo stem height which are correlated with yield. The fresh and dry yield of rhizomes of V I and V 2 were found to be on par with V 8 the highest fresh rhizome yielder and V 10 the highest dry rhizome yielder. V 3, a variant from Himachal Pradesh also produced yield on par with the highest yielder. The yielding capacity of the autotetraploids especially V 2 was found to be superseded by the incidence of diseases like soft rot and bacterial wilt. V I was least susceptible to leaf spot. V 10 (Himachal Pradesh) showing stable performance over the years had low incidence of soft rot and bacterial wilt. The high pollen fertility arid viability of the autotetraploids V I and V 2 and the highest pollen size and tube length observed in V 2 make them ideal as pollen parents in hybridization programmes. None of the various in vivo pollination techniques such as stylar, stigmatic, intra ovarian was effective for inducing fruit set or seed set in ginger.